(untitled) (International Current Pharmaceutical Journal, 2016)
Viral hepatitis is one of the common transmissible causes of chronic liver responsible for increased risk of mortality and morbidity. Hepatitis C disease has worldwide high prevalence which is more fatal because of lack of vaccination availability. Present study was conducted with the aim of to address the comparative prevalence and risk factor of hepatitis C. Secondary objective was to evaluate the prevalence of this disease in Pakistan as compared to other countries. Most of the countries in the world do not have significant studies of population infected with Hepatitis C virus (HCV). During 1990-2016, 232 studies were included; containing 117 countries representing that 90% of the world population have 2.3% prevalence. According to studies, developed countries have low HCV prevalence while developing countries have high prevalence. Pakistan being a developing country has second highest HCV prevalence ranging from 4.5 to 8%. The reason of this high prevalence is unawareness about Hepatitis C in community and lack of successful therapies for patients with HCV. In past, developed countries had high prevalence but now they have low incidence because of proper system and awareness. Pakistan needs such kind of public awareness programs and better treatment facilities at affordable price to community. Tahir et al., International Current Pharmaceutical Journal, November 2016, 5(12): 106-110 http://www.icpjonline.com/documents/Vol5Issue12/02.pdf